2015
DOI: 10.1371/journal.pone.0119109
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Count and Early Outcome in Patients with Spontaneous Cerebellar Hemorrhage: A Retrospective Study

Abstract: IntroductionThe importance of coagulation, hematology, and biochemical variables have been investigated in the stroke population but have not been systemically surveyed in cerebellar hemorrhage (CH) population. The aim of the study was to explore the predictive value of these factors for early outcome in this population.Materials and MethodsEighty patients with acute spontaneous CH were retrospectively analyzed. Clinical and laboratory data were collected on admission for analysis. The patients were divided by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…The SCH volumes were calculated the area occupied by the hyperdense hematoma with the ABC/2 formula in the initial brain CT. In the formula, A indicated the largest diameter of hemorrhage by CT, B indicated the largest diameter perpendicular to A, and C indicated the CT slice thickness multiplied by the number of CT slices of the hemorrhage [10, 15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SCH volumes were calculated the area occupied by the hyperdense hematoma with the ABC/2 formula in the initial brain CT. In the formula, A indicated the largest diameter of hemorrhage by CT, B indicated the largest diameter perpendicular to A, and C indicated the CT slice thickness multiplied by the number of CT slices of the hemorrhage [10, 15].…”
Section: Methodsmentioning
confidence: 99%
“…The patients were divided into two groups according to the discharge outcome: 1) The good outcome group with independent performance of daily activities (Glasgow Outcome scale (GOS) score = 4 or 5). 2) The poor outcome group with disability of daily living, vegetative states, or death (GOS score = 1, 2, or 3) [10]. .…”
Section: Methodsmentioning
confidence: 99%
“…Modification of platelet function and consequently a hypercoagulable state has been suggested in patients with both ischemic and hemorrhagic strokes [8]. It has been shown that PC and MPV are independent predictors for poor outcome in primary intracerebral hemorrhage (PICH) [9]. There has also been a body of interest for PC and MPV in stroke patients.…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous intracerebral hemorrhage accounts for 10–15% of all strokes and has a high mortality rate of 19% within the first month [1]. It is the least common type of intracranial hemorrhage, representing 5–10% of all intracerebral hemorrhages, and it is associated with high mortality rates of 20% to 75%, irrespective of treatment [2,3].…”
Section: Introductionmentioning
confidence: 99%